Near-infrared emission in Ho3+-doped Yb3Ga5O12 garnet nanocrystals - Netolický, Tomáš; Beneš, Ludvík; Melánová, Klára; Šlang, Stanislav; Oswald, J; Wágner, Tomáš (Elsevier Science BV, 2022)
The single-phase Ho3+-doped Yb3Ga5O12 garnet nanocrystals were synthesized by the sol-gel combustion technique using citric acid. Their structure, morphology and chemical composition were examined by the powder X-ray diffraction, attenuated total reflectance-Fourier transform infrared spectroscopy and Energy-dispersive X-ray spectrometry with the scanning electron microscope. The observed strong absorption band associated with the high content of Yb3+ ensures efficient excitation of the Yb15-xHoxGa25O60 garnets using 980 nm radiation. The near-infrared emission originating from the Ho3+: 5I6 -> 5I8 and 5I7 -> 5I8 transitions is studied using the measurement of the steady-state and time-dependent emission spectra. The proposed luminescence mechanism is discussed based on the Yb3+ -> Ho3+ energy transfer with contribution of the Ho3+ -> Yb3+ energy back transfer and Ho3+ & harr; Ho3+ cross-relaxation processes.
Blízká infračervená emise v Ho3+ dopovaném Yb3Ga5O12 nanokrystalickém granátu
Keywords: Yb3Ga5O12 garnet; Ho3+-doped garnet; Near -infrared emission; Lifetime; Sol -gel combustion; Yb3Ga5O12 granát; Ho3+-dopovaný granát; emise v blízké infračervené oblasti; Lifetime; Sol -gel spékání